Functional stratification and enzymatic arrangement in microbial communities across a hypersaline depth gradient - Hoepfner, Claudia; Guzmán, Daniel; Vidal-Veuthey, Boris; Foronda, Valeria; Beggs, Antonia; Cárdenas, Juan P.; Vargas, Virginia A.; Alfaro, Fernando D. (Frontiers in Microbiology, 2025)
Extreme environments comprise a significant portion of Earth’s terrestrial surface, posing challenges, such as extreme temperatures, pressure, pH extremes, oxygen and nutrient scarcity, and high salinity. Hypersaline ecosystems, such as those in the Andean Cold Deserts, exemplify extreme environments where microbial life has evolved specialized survival mechanisms. The Central Andean Mountains host extensive salt flats exposed to extreme temperature fluctuations, intense ultraviolet radiation, and high soil salinity. While most studies focus on surface layers, the impact of soil depth on functional diversity remains poorly understood. This study utilized shotgun metagenomics and functional annotation to explore enzymatic diversity across a 8-meter depth gradient in the Uyuni Salt Flat aiming to understand microbial adaptations to depth and abiotic stress. Our findings revealed a complex, stratified microbial ecosystem. Surface layers showed high abundance of amylases, enzymes that degrade accessible carbohydrates, likely derived from photosynthetic communities or surface-imported organic matter. These patterns suggest a dominance of strategies for rapid carbon decomposition. Intermediate depths exhibited elevated lipase and peroxidase activity, reflecting the presence of complex lipids and oxidative stress management, essential for survival in oxygen-limited, high-salinity zones. Lipase support lipid utilization as a carbon source, while peroxidase activity points to redox adaptations for microbial resilience under fluctuating oxidative conditions. Deeper sediment layers showed a shift toward protease and peptidase activity, indicating organic nitrogen recycling in nutrient-deprived environments and suggesting an efficient protein degradation system among halophilic archaea. Peroxidases remained abundant even at these depths, supporting sustained redox regulation and biogeochemical cycling thus enabling microbes to manage redox imbalances in high-salinity, low-oxygen settings. The enzymatic diversity across the depth gradient demonstrates functional stratification and remarkable microbial adaptability to hypersaline conditions. This functional resilience underpins nutrient cycling and organic matter decomposition deep in the salt flats. Notably, the identified halophilic enzymes, stable and active under high-salinity conditions, hold significant potential for biotechnological applications. This study contributes to our understanding of microbial life’s complexity in hypersaline environments, enhancing our ability to harness extremophilic enzymes for biotechnological applications while underscoring the ecological value of these unique habitats.